The Effect of Pineapple Crude Enzymes and Fermentation Time on The Decaffeination Process of Robusta Coffee - Hariyadi, Tri; Paramitha, Tifa; Irmawati, Dwi; Salsabila, Salwa Ainaya (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
The decaffeination of robusta coffee can be done through fermentation with a crude enzyme containing bromelain enzyme from pineapple. The study aims to determine the activity of the bromelain enzyme by the Kunitz method, the effect of fermentation time and crude enzyme concentration on the decaffeination process, and the characteristics of coffee before and after fermentation using FTIR. The fermentation time was varied from 6 to 36 hours and the crude enzyme concentration was varied from 10 to 80%. The activity of the bromelain enzyme was 36 U/ml. Fermentation time affects the decaffeination process, wherein the longer the fermentation time from 6 hours to 36 hours obtained caffeine content from 2.39% to 0.07%. Besides that, the crude enzyme concentration affects the decaffeination process, which obtained the lowest caffeine content or percent decaffeination at the crude extract concentration of 80% (v/v). FTIR results showed that the decaffeination process affected the reduction of caffeine in coffee samples. It can be shown from the increase in the %T value of the C-N functional group from 40.731 to 54.85.